Dieless incremental forming using 3-axis CNC milling machine for aluminium sheet - Shea, Cheng Kuang (2016)
Incremental sheet forming is a versatile sheet metal forming process where a sheet metal is formed into its final shape by a series of localized deformation without a specialised die. However, it still has many shortcomings that need to be overcome such as geometric accuracy, surface roughness, formability, forming speed, and so on. This project focus on minimising the surface roughness of aluminium sheet and improving its thickness uniformity in incremental sheet forming via optimisation of wall angle, feed rate, and step size. Besides, the effect of wall angle, feed rate, and step size to the surface roughness and thickness uniformity of aluminium sheet was investigated in this project. First of all, part design and tool path generation were done in CATIA software to form the shape of pyramid frustum. Then, the blank holder and the forming tool made of mild steel were fabricated afterwards. Through the selected design of experiments, the incremental sheet forming experiments were carried out on a 3-axis CNC milling machine. From the results, it was observed that surface roughness and thickness uniformity were inversely varied due to the formation of surface waviness. Increase in feed rate and decrease in step size will produce a lower surface roughness, while uniform thickness reduction was obtained by reducing the wall angle and step size. By using Taguchi analysis, the optimum parameters for minimum surface roughness and uniform thickness reduction of aluminium sheet were determined. Meanwhile, analysis of variance concluded that step size is the most significant parameter to both the surface roughness and thickness uniformity of aluminium sheet in incremental sheet forming. The finding of this project helps to reduce the time in optimising the surface roughness and thickness uniformity in incremental sheet forming.